2017
DOI: 10.3389/fneur.2017.00612
|View full text |Cite
|
Sign up to set email alerts
|

Role of Perinatal Inflammation in Neonatal Arterial Ischemic Stroke

Abstract: Based on the review of the literature, perinatal inflammation often induced by infection is the only consistent independent risk factor of neonatal arterial ischemic stroke (NAIS). Preclinical studies show that acute inflammatory processes take place in placenta, cerebral arterial wall of NAIS-susceptible arteries and neonatal brain. A top research priority in NAIS is to further characterize the nature and spatiotemporal features of the inflammatory processes involved in multiple levels of the pathophysiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
57
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 129 publications
(224 reference statements)
2
57
0
Order By: Relevance
“…Only a few case-control studies have aimed to specify risk factors; however, the number of cases was relatively low and there is little consistency in the observed maternal, obstetric, and neonatal risk factors [7,13,14]. The only independent risk factor, which appeared in all case-control studies, was perinatal inflammation, while genetic prothrombotic disorders were not found to be associated with the frequency of NAIS [3].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Only a few case-control studies have aimed to specify risk factors; however, the number of cases was relatively low and there is little consistency in the observed maternal, obstetric, and neonatal risk factors [7,13,14]. The only independent risk factor, which appeared in all case-control studies, was perinatal inflammation, while genetic prothrombotic disorders were not found to be associated with the frequency of NAIS [3].…”
Section: Introductionmentioning
confidence: 99%
“…NAIS generally occurs in term neonates and presents a major risk for life-long motor, cognitive, and/or behavioral disabilities ranging from fine motor impairments to unilateral cerebral palsy, which develops in around 20-30% of affected neonates. Thus NAIS is a leading cause of cerebral palsy [3].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations